Domain engineering and full matrix material constants of the [111]c-poled 0.63Pb(Mg1/3Nb2/3)-0.37PbTiO3 single crystal. Issue 33 (25th July 2018) - Yuan, Zhongyuan; Sang, Shijing; Sun, Enwei; Qi, Xudong; Chang, Wei-Yi; Zhang, Rui; Yang, Bin; Jiang, Xiaoning; Cao, Wenwu
Abstract : Domain engineering was performed on a [111]c -oriented tetragonal ferroelectric 0.63Pb(Mg1/3 Nb2/3 )-0.37PbTiO3 (PMN-0.37PT) single crystal in order to achieve better piezoelectric properties. Abstract : Domain engineering was performed on the [111]c -oriented tetragonal ferroelectric 0.63Pb(Mg1/3 Nb2/3 )-0.37PbTiO3 (PMN-0.37PT) single crystal in order to achieve better piezoelectric properties. Influences of the poling electric field ( E P ), poling temperature, and poling time on piezoelectric and electromechanical properties were investigated. The piezoelectric and dielectric constants increase with increasing the E P . In addition, the piezoelectric response increases with increasing the poling time but the crystal saturates after 10 min of poling at 30 °C or 20 min at 150 °C under E P = 2 kV mm −1 . The piezoelectric strain coefficient d 33 can be improved from 407 pC N −1 poled at 30 °C to 706 pC N −1 after poling at 150 °C near T C, which is 27.9% higher than the highest value reported before ( d 33 = 551.9 pC N −1 ). The enhancement of piezoelectric response results from the domain structure redistribution occurring near the ferroelectric to paraelectric phase transition temperature because the potential barrier is substantially lowered so that polarization switching becomes easier. Therefore, more domain walls appear to be beneficial for the enhancement of the piezoelectric response. Under the optimized poling conditions, a complete set of dielectric, elastic, and piezoelectric constants was measured for [111]c -poled PMN-0.37PT single crystal using a combined resonance and ultrasonic method (CRUM). Both the longitudinal ( d 33 = 706 pC N −1 ) and shear ( d 15 = 875 pC N −1 ) piezoelectric properties are outstanding for the [111]c -poled PMN-0.37PT single crystal due to domain wall motions.